ANALYSIS OF STUDENT PRACTICAL USING LOGGER PRO TO IMPROVE GRAPHIC REPRESENTATION OF HARMONIC OSCILLATION MATERIAL - Dewi, Adelina Ryan Candra; Susilo, Susilo; Putra, Ngurah Made Dharma (Universitas Negeri Semarang, 2018)
This study aims to analyze the activities of computational practicum using logger pro software to improve student graphic representation in understanding the oscillation material. The sample are 35 students of class X Mipa 3 SMA 1 Bae in 2016/2017 decided by purposive sampling technique. The research instrument is a harmonic oscillation sheet and a description test that measures the ability of graphical representation. The research method used mixed method with concurent embeded design. Analysis of research data using comparative test t paired sample test and N - Gain test of student scores. Students found some synchronous oscillation characteristics between the results of the lab and the results of the analysis of six graphs from the plot logger pro. The results of pretest and post-test average score are respectively 20.85 and 43.73. Description of comparative test statistic yields tcount> ttable which means there is significant difference between pre-test and post-test value data, and N-Gain test is 0.29 which means there is increasing value in low category. It shows computational activity using logger pro, effectively improving students' ability in multiple graph representations to understand the characteristics of harmonic oscillations.